New Anthraquinones from the Roots of Hedyotis dichotoma - Hamzah, Ahmad Sazali; Jasmani, H; Ahmad, R.; Baba, A R; Lajis, N.H; Aimi, N; TAKAYAMA, H.; Kitajima, M.
Two new anthraquinones, 1,4-dihydroxy-2,3-dimethoxyanthraquinone (1) and 2,3-dimethoxy-9-hydroxy-1,4-anthraquinone (2), were isolated from the roots of Hedyotis dichotoma along with two known plant metabolites, isovitexin and ursolic acid. The structures of 1 and 2 were elucidated using spectroscopic techniques.